2010
DOI: 10.3109/17482968.2010.515223
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of the cervical cord in amyotrophic lateral sclerosis

Abstract: The objective of this study was to use magnetic resonance spectroscopy (MRS) to compare metabolite ratios in the cervical spinal cord of ALS patients to healthy controls. Fourteen ALS patients and 16 controls were scanned using a 3T scanner. A rectangular voxel (8 × 5 × 35 mm) was placed along the main axis of the cord with the lower limit at the inferior aspect of the C2 vertebral body. MRS was performed with a point-resolved spectroscopy (PRESS) sequence. Water signals were suppressed using a three-pulse che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
2
36
2
Order By: Relevance
“…Cooke et al 5 recommended a voxel size of 9 ϫ 7 ϫ 35 mm 3 and appropriate placement so that the lower limit of the voxel level is aligned with the inferior border of the C2 vertebral body. In some investigations, the voxel dimensions are kept constant but smaller than the previously recommended size, to ensure that the voxel size fits even in subjects with a small spinal cord diameter, 9,14,19,22,29,30,33,36,37 whereas others adapt the voxel size to each individual subject. 17,18,20,21 Edden et al 26 introduced 1D…”
Section: Voxel Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooke et al 5 recommended a voxel size of 9 ϫ 7 ϫ 35 mm 3 and appropriate placement so that the lower limit of the voxel level is aligned with the inferior border of the C2 vertebral body. In some investigations, the voxel dimensions are kept constant but smaller than the previously recommended size, to ensure that the voxel size fits even in subjects with a small spinal cord diameter, 9,14,19,22,29,30,33,36,37 whereas others adapt the voxel size to each individual subject. 17,18,20,21 Edden et al 26 introduced 1D…”
Section: Voxel Placementmentioning
confidence: 99%
“…They noticed a decrease of the NAA/Cr ratio and an increase of Cho/NAA in patients, without presentingquality indicators apart from 2 exemplary spectra with relatively low SNR. Carew et al 22 and Pineda-Alonso et al 28 used their previously published methods 27 to investigate amyotrophic lateral sclerosis in 14 patients (On-line Table 2) and 16 controls (On-line Table 1). They could show that NAA/Cr and NAA/myo-inositol were reduced in patients with amyotrophic lateral sclerosis, and the reduction correlated significantly with clinical parameters.…”
Section: Mr Spectroscopy Of the Human Spinal Cord: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study size represented all available data as of March 2010. As described previously, 10 the subjects with ALS were recruited from the Emory University EMG laboratory, an ongoing clinical trial of arimoclomol in SOD1ϩ familial ALS as well as people with ALS who are registered with the Muscular Dystrophy Association. The healthy controls were recruited from several sources including spouses and other relatives of patients with ALS and a registry of healthy subjects maintained by one of the investigators (M.B.)…”
mentioning
confidence: 99%
“…A number of studies have demonstrated a reduction in N-acetylaspartate (NAA), a marker of neuronal loss, in patients with ALS compared to controls expressed as absolute concentrations, 11,12 or as ratios of other metabolites like choline (Cho) and creatine (Cr) 10,[13][14][15][16][17][18][19][20][21][22][23][24] in the primary motor cortex, 13,17,19,23,25,26 centrum semiovale, internal capsule, corticospinal tract, cervical spine, 10,12,23 medulla, 5 and brainstem. Whether similar findings might be evident in people at risk for developing ALS, however, remains an unanswered question.…”
mentioning
confidence: 99%